Strategic Issues of the Position of the President 3 Period In the Perspective of State Constitutional Law in the Restriction of Power - Abrillioga Abrillioga; Aldian Nugraha; Azzam. H. F; Himy Oktafiansyah (Green Publisher Indonesia, 2022)
The subject of extending the presidential term to three terms is one that all of us are concerned about. In this example, in the contestation of the dynamics of government and politics in Indonesia, the discourse of the desire to change the 1945 Constitution aims to homogenize the discourse views of the interests of power, making this an intriguing subject to research. As a concept of preventing the authoritarian pendulum in a country, it is required to limit the power held by a head of state and head of government, particularly the president. The term of office for presidential candidates in Indonesia is controlled by the country's presidential system of government. Like the current dynamics in the Indonesian government, that dilemmas and conflicts of interest stemming from pragmatic reasons for legal politics in Indonesia appear to want to smoothen the constitution, namely Article 7 of the 1945 Constitution, which has limitedly affirmed the limits of positions held by a president, namely two terms. by using the provisions of the original intense article 37 of the 1945 Constitution to delegate to three terms. In essence, the presidential term restriction is intended to prevent abuse of power.